PENGEMBANGAN DAN PENERAPAN APLIKASI NUTRI-GRADE DI PUSKESMAS CIMARAGAS UNTUK MENDUKUNG EDUKASI DAN PEMANTAUAN GIZI MASYARAKAT - Chalifa Chazar,; Muchammad Fahrizal,; Yoga Ramadhan,; Miftah Nugraha,; Tegar Akmal,; Shavinko Izumi Henryka, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program addresses the issue of limited public awareness regarding nutritional balance in food consumption, as highlighted in the background of the activity. The program aims to develop NutriGrade, a mobile application leveraging AI technology to scan and simplify nutritional label information, making it more accessible and engaging for users. Using the Agile development methodology, the project proceeded through planning, design, feature implementation, testing, and maintenance phases. The application was tested among diverse user groups, demonstrating its effectiveness in increasing nutritional understanding, supporting healthier consumption habits, and aligning with smart city objectives by integrating advanced technology into daily life. This initiative successfully contributed to public health awareness by enabling informed dietary choices, thus reducing the risks associated with malnutrition, obesity, and related health issues.